Assessing Heat Resistance and Selecting Heat-Resistant Individuals of Largemouth Bass (Micropterus salmoides) with Tiered Thermal Exposure - Haijie Chen; Hui Qiao; Zhicheng Xv; Guili Song; Shuning Liu; Cheng Luo; Yong Long; Shimei Lin (Animals)
Largemouth bass (LMB, Micropterus salmoides), a commercially important farmed fish, is vulnerable to heat stress. Breeding heat-resistant LMB is highly desirable in the face of global warming. However, we still lack an efficient method to assess the heat resistance of LMB. In this study, the critical thermal maximum (CTmax) and static exposure methods were first performed to assess the heat resistance of LMB juveniles. The CTmax values of the experimental fish (average body weight 9.87 ± 3.14 g) ranged from 39 to 40 °C but were too close together to differentiate the individual heat resistance. Static exposure experiments with varying temperatures and fish groups also did not provide a clear method for determining the heat resistance. To address these limitations, we developed a tiered exposure method, where the temperature was increased step-wise, starting from 28 to 34 °C at 2 °C increments and then at 0.5 °C increments above 34 °C, with each step lasting one day. The heat resistance of the fish was quantified as the lethal cumulative temperature (LCT), allowing for the classification of fish as sensitive or resistant to heat stress based on their LCT values. To correlate the changes in tissue structure and gene expression with the heat resistance, a new batch of LMB juveniles (average body weight 23.66 ± 6.98 g) were subjected to tiered heat exposure. Brain and liver tissues were collected from the control (without heat exposure), resistant and sensitive (still alive but demonstrated abnormal symptoms) individuals when the temperature was maintained at 35.5 °C for 24 h. The liver tissues of the heat-sensitive individuals showed significant damage and increased cell apoptosis (p < 0.05) relative to those of the resistant ones. The ddit3/chop, bax and casp3 genes demonstrated differential expressions in the liver of the sensitive and resistant fish. Additionally, the LMB juveniles (average body weight 84.06 ± 20.95 g) were found to be more heat resistant than the adults from different sources (average body weight 364.29 ± 84.43 g and 545.71 ± 184.56 g). Through the tiered exposure method, extremely heat-resistant individuals were successfully selected from the population (average body weight 22.69 ± 6.89 g). These findings provide valuable insights into the thermal biology of LMB and the potential for breeding heat-resistant LMB varieties.